Law Enforcement of Traffic Violations in Sidoarjo Regency: Penegakan Hukum Pelanggaran Lalu Lintas di Kabupaten Sidoarjo - Syaifullah, Achmad Firman; Rosnawati , Emy (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Traffic violations remain a persistent issue in urban areas of Indonesia, reflecting both human behavior and the challenges of law enforcement. Specific Background: In Sidoarjo Regency, the rise in traffic violations and accidents highlights weaknesses in the current legal enforcement system and public awareness. Knowledge Gap: Previous studies have focused mainly on the regulatory framework without assessing the practical alignment between legal procedures and societal needs. Aims: This study analyzes the legal enforcement of minor traffic offenses in Sidoarjo, evaluating public compliance, enforcement consistency, and institutional cooperation under Law Number 22 of 2009. Results: The findings indicate that the effectiveness of law enforcement depends on the availability of resources, public legal awareness, inter-agency collaboration, and adaptive procedures that align with local realities. Novelty: Unlike earlier research, this study integrates juridical-sociological analysis with empirical field data to examine adaptive enforcement mechanisms at the local level. Implications: The research underscores the need for continuous policy innovation, improved coordination among legal institutions, and community-based education to strengthen traffic law compliance. Highlights: Identifies core factors affecting traffic law enforcement in Sidoarjo. Integrates juridical-sociological and empirical approaches. Emphasizes adaptive, community-oriented legal strategies. Keywords: Law Enforcement, Traffic Violations, Legal Awareness, Sidoarjo, Public Policy